Left ventricular function in endurance runners during exercise - Jensen-Urstad, M.; Bouvier, F.; Nejat, M.; Saltin, B.; Brodin, L. A. (Acta Physiologica Scandinavica, 1999)
Left ventricular function in elite runners and controls was compared by means of nuclear angiocardiography. Fifteen middle- or long-distance runners and a control group of 10 sedentary to moderately physically active subjects were studied at rest and during semi-sitting incremental exercise. Ejection fraction was higher in the runners than the controls both at rest and during exercise. At the transition from rest to exercise left ventricular end-diastolic volume initially increased similarly in runners and controls by an average of 14 and 12%, respectively, with an increase in stroke volume by approximately 25 and 23%. The parallel increase in stroke volume and left ventricular end-diastolic volume could at least partly be because of the Frank-Starling mechanism. With increasing workloads, left ventricular end-diastolic volume and ejection fraction remained fairly constant, resulting in an unchanged stroke volume from the lowest to the highest exercise intensity. This was in the runners accomplished by a 41% increase in peak filling rate and a 38% increase in peak emptying rate with similar changes observed in the controls. This has to be due to increased myocardial contractility paralleling the systolic shortening with increasing heart rate. We conclude that endurance-trained athletes have a better systolic function expressed as higher ejection fraction both at rest and during exercise than untrained subjects reflecting an enhanced myocardial contractility contributing to the maintenance of a large stroke volume during exercise. The regulatory mechanisms however, appear to be similar for athletes and healthy controls.